A trial of recombinant human granulocyte colony stimulating factor for the treatment of very low birthweight infants with presumed sepsis and neutropenia. Issue 3 (1st May 2001) - Russell, A R Bedford; Emmerson, A J B; Wilkinson, N; Chant, T; Sweet, D G; Halliday, H L; Holland, B; Davies, E G
Abstract : OBJECTIVES: The primary objective was to investigate the safety of recombinant human granulocyte colony stimulating factor (rhG-CSF) for the treatment of very low birthweight infants (VLBW) with sepsis and relative neutropenia, specifically with regard to worsening of respiratory distress and thrombocytopenia and all cause mortality. Secondary objectives were to evaluate duration of ventilation, intensive care, and antibiotic use as markers of efficacy. DESIGN: Neonates (⩽  28 days) in intensive care, with birth weights of 500–1500 g, absolute neutrophil count (ANC) of ⩽ 5 × 10 9 /l, and clinical evidence of sepsis, were randomly assigned to receive either rhG-CSF (10 μg/kg/day) administered intravenously (n = 13), or placebo (n = 15) for a maximum of 14 days, in addition to standard treatment and antibiotics. All adverse events, oxygenation index, incidence of thrombocytopenia, all cause mortality, duration of ventilation, intensive care and antibiotic treatment, and ANC recovery were compared between the two groups. RESULTS: Adverse events and oxygenation index were not increased by, and thrombocytopenia was not attributable to, treatment with rhG-CSF. At 6 and 12 months postmenstrual age, there were significantly fewer deaths in the group receiving rhG-CSF (1/13 v 7/15; p ⩽ 0.038). There was a non-significant trend towards a reduction in duration of ventilation, intensive care, and antibiotic use in the rhG-CSF group. There was a significantly more rapid increase in ANC in the rhG-CSF treated babies (p < 0.001). CONCLUSIONS: In a small randomised placebo controlled trial in a highly selected group of neonates, adjuvant treatment with rhG-CSF increased ANC rapidly, and no treatment related adverse events were identified. Mortality at 6 and 12 months postmenstrual age was significantly lower in the treatment group. A large trial investigating efficacy in a similar group of neonates is warranted.